The origin and insecticide resistance of Aedes albopictus mosquitoes established in southern Mozambique - Sarina Yamashita; Kawane Uruma; Chao Yang; Yukiko Higa; Noboru Minakawa; Nelson Cuamba; Kyoko Futami (Parasites & Vectors, 2024)
Abstract Background The Aedes albopictus mosquito is of medical concern due to its ability to transmit viral diseases, such as dengue and chikungunya. Aedes albopictus originated in Asia and is now present on all continents, with the exception of Antarctica. In Mozambique, Ae. albopictus was first reported in 2015 within the capital city of Maputo, and by 2019, it had become established in the surrounding area. It was suspected that the mosquito population originated in Madagascar or islands of the Western Indian Ocean (IWIO). The aim of this study was to determine its origin. Given the risk of spreading insecticide resistance, we also examined relevant mutations in the voltage-sensitive sodium channel (VSSC). Methods Eggs of Ae. albopictus were collected in Matola-Rio, a municipality adjacent to Maputo, and reared to adults in the laboratory. Cytochrome c oxidase subunit I (COI) sequences and microsatellite loci were analyzed to estimate origins. The presence of knockdown resistance (kdr) mutations within domain II and III of the VSSC were examined using Sanger sequencing. Results The COI network analysis denied the hypothesis that the Ae. albopictus population originated in Madagascar or IWIO; rather both the COI network and microsatellites analyses showed that the population was genetically similar to those in continental Southeast Asia and Hangzhou, China. Sanger sequencing determined the presence of the F1534C knockdown mutation, which is widely distributed among Asian populations, with a high allele frequency (46%). Conclusions These results do not support the hypothesis that the Mozambique Ae. albopictus population originated in Madagascar or IWIO. Instead, they suggest that the origin is continental Southeast Asia or a coastal town in China. Graphical Abstract